2023
DOI: 10.1021/acsanm.3c03250
|View full text |Cite
|
Sign up to set email alerts
|

Cubic- and Hexagonal-Phase MgZnO Nanoparticles for Electron Transport Layers in Electroluminescent Quantum-Dot Light-Emitting Diodes

Abstract: Magnesium-doped zinc oxide (MZO) nanoparticles (NPs) with a cubic zinc blende (ZB) structure and with a hexagonal wurtzite (WZ) structure were prepared via a wet-chemical synthetic process by varying the base and used as the electron transport layer (ETL) for electroluminescent (EL) quantum-dot light-emitting diodes (QLEDs). Both as-synthesized MZO NPs were monodisperse with a polydispersity index <0.15 and retained excellent colloidal stability at least for 4 weeks. The formation of a NP film from the MZO NPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…It has been reported that the device operational time could be improved by more efficient electron–hole injection into the QD emitting layer (EML) . On the other hand, it was reported that a carrier-transport layer with appropriate roughness could improve the charge injection, so improved reliability of the NaCl-doped PVK HTL might also be related to enhanced carrier injection. Parts b and c of Figure present the turn-on voltage and current efficiency data of QLEDs with various NaCl doping contents.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the device operational time could be improved by more efficient electron–hole injection into the QD emitting layer (EML) . On the other hand, it was reported that a carrier-transport layer with appropriate roughness could improve the charge injection, so improved reliability of the NaCl-doped PVK HTL might also be related to enhanced carrier injection. Parts b and c of Figure present the turn-on voltage and current efficiency data of QLEDs with various NaCl doping contents.…”
Section: Resultsmentioning
confidence: 99%
“…The device data are summarized in Table . In this work, QDs with a relatively thicker shell are employed in the devices, which exhibit much higher current density than conventional QDs with a thinner shell. These types of QDs can be driven to exhibit high brightness but with relatively lower external quantum efficiency (EQE) because of higher current consumption. After the introduction of a NaCl-doped PVK HTL, the device efficiency obviously increases, and the driving voltage decreases as well.…”
Section: Resultsmentioning
confidence: 99%
“…15–17 They have also tried to use CQD films as an active material for field effect transistors 18 and solar cells, 19 and as a self-emitting layer for the CQD-electroluminescence (EL) device structure. 20 With their massive Stokes shift, strong photoluminescence quantum yield (PLQY), and high extinction coefficient across a broad-spectrum range, CQDs are becoming a more popular choice in science for use in a wide range of optoelectronic device designs. 21 Recent advances in CQD nanotechnology have also slowly introduced these nanomaterials into analytical areas mostly as chemical sensors in fluorescence-based measurements.…”
Section: Introductionmentioning
confidence: 99%